Portfolio Flows Into India : Do Domestic Fundamentals Matter? - Gupta, Poonam (IMF Working Papers; Working Paper ;, 2003)
This paper analyzes the factors affecting portfolio equity flows into India using monthly data. Flows to India are small compared to other emerging markets, but seem to be relatively less volatile. They also seem to be quite resilient. The paper shows that portfolio flows are determined by both external and domestic factors. Among external factors, LIBOR and emerging market stock returns are important, while the primary domestic determinants are the lagged stock return and changes in credit ratings. In quantitative terms, both external and domestic factors are found to be about equally important.